Natural Convection Flow with Combined Buoyancy Effects Due to Thermal and Mass Diffusion in a Thermally Stratified Media - S. C. Saha; M. A. Hossain (Nonlinear Analysis, 2004)
We present here a numerical study of laminar doubly diffusive free convection flows adjacent to a vertical surface in a stable thermally stratified medium. The governing equations of mass, momentum, energy and species are non-dimensionalized. These equations have been solved by using an implicit finite difference method and local non-similarity method. The results show many interesting aspects of complex interaction of the two buoyant mechanisms that have been shown in both the tabular as well as graphical form.